Genomic Analysis of Antibiotic-Resistant Staphylococcus epidermidis Isolates From Clinical Sources in the Kwazulu-Natal Province, South Africa - Asante, Jonathan; Hetsa, Bakoena A.; Amoako, Daniel G.; Abia, Akebe L. K.; Bester, Linda A.; Essack, Sabiha Y. (Frontiers in Microbiology, 2021)
Staphylococcus epidermidis has become an important nosocomial pathogen. Methicillin and multidrug resistance make S. epidermidis infections difficult to treat. The study aims to describe the genomic characteristics of methicillin-resistant S. epidermidis (MRSE) isolated from clinical sources, to comprehend the genetic basis of antibiotic resistance, virulence and potential pathogenicity. Sixteen methicillin-resistant S. epidermidis (MRSE) were characterized by whole-genome sequencing and bioinformatics analysis to ascertain their resistome, virulome, mobilome, clonality and phylogenomic relationships. In all, 75% of isolates displayed multidrug resistance and were associated with the carriage of multiple resistance genes including mecA, blaZ, tet(K), erm(A), erm(B), erm(C), dfrG, aac(6')-aph(2'') and cat(pC221) conferring resistance to β-lactams, tetracyclines, macrolide-lincosamide-streptogramin B, aminoglycosides and phenicols, that were located on both plasmids and chromosomes. Their virulence profile evidenced genes involved in adherence/biofilm formation (icaA, icaB, icaC, atl, ebh, ebp), immune evasion (adsA, capC, manA) and antiphagocytosis (rmlC, cdsA, cpsA). The community-acquired SCCmec_type_IV was the most common SCCmec type. The CoNS belonged to seven multilocus sequence types (MLSTs) and carried a diversity of mobile genetic elements such as phages, insertion sequences and plasmids. The bacterial anti-phage defense systems CRISPR-Cas immunity phage system and Restriction-Modification System (R-M system) and the Arginine Catabolic Mobile Element (ACME) involved in immune evasion and transport of virulence genes were also found. The insertion sequence, IS256, linked with virulence, was found in 56.3% of isolates. Isolates were organized into two major clades with some similarity but also considerable variability within isolates. Whole-genome sequencing and bioinformatics analysis provide insights into the likely pathogenicity and antibiotic resistance of S. epidermidis, necessitating surveillance of this emerging pathogen.